New bacteria genera associated with rice (Oryza sativa L.) in Cuba promote the crop growth - Hernández-Forte, Ionel (2022)
Introduction. The rice cultivar INCA LP-7 is one of the eleven principal cultivars in Cuba due to their high yield potential, salinity tolerance, and pathogens resistance. However, there are not reports about the isolation, identification, and characterization of bacteria associated to this cultivar that promote its growth. Objective. To select promising bacteria from the rhizosphere of the INCA LP-7 rice cultivar to promote the crop growth. Materials and methods. The investigation was carried out in 2015 and 2016 at the Instituto Nacional de Ciencias Agropecuarias, Cuba and Instituto de Investigaciones Biologicas Clemente Estable, Uruguay. The 16SrNA gene of bacteria associated with the INCA LP-7 rice cultivar was isolated and identified by sequencing. Characterization was performed as plant growth promoting bacteria and the effect of bacterial inoculation on rice growth was studied. Results. Eleven rizopheric bacteria were isolated from rice plants of the INCA LP-7cultivar. A phylogenetic analysis showed that for the first time in Cuba Pantoea, Acinetobacter, and Mitsuaria genera were reported associated with rice. Rhizobium and Enterobacter genera were also informed as rhizospheric bacteria of INCA LP-7 rice cultivar. Some isolates solubilize inorganic phosphates and potassium, produce siderophores and indolic compound, had exo-celulase and protease activity and formed biofilm. The inoculation of isolates belonging to Pantoea genus produced an increase in height, root length, and biomass of rice plants under greenhouse conditions. Conclusions. Pantoea sp. GG1 and Pantoea sp. GG2 were the most promising strains for the inoculation of the INCA LP-7 rice cultivar. This is the first report in Cuba that focuses on the characterization of the bacterial microbiota part associated to Cuban rice cultivar INCA LP-7 and reports bacteria of the Pantoea genus as crop growth promoters.